DESIGN AND FABRICATION OF ROTOR WINDMILL WATER PUMPING - CHAIB, Nasreddine; REZIG, Ahmida (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE Département de génie mécanique, 2023)
This study focuses specifically on utilizing wind power to generate mechanical energy for the purpose of water pumping. It aims to address the water needs of isolated sites, particularly in the windy areas of the Algerian highlands. The main goal of this project is to design and construct a windmill rotor that can be used for water pumping, with a primary focus on assisting and easing the challenges faced by small-scale farmers. To begin the project, we conducted an extensive review of literature that encompassed different types of wind turbines, their operating principles, key components, and their characteristics. Following that, we developed a strategy for designing and calculating the various components of the windmill rotor. Lastly, we focused on the practical realization of the wind turbine rotor, encompassing the manufacturing stages of its components.
Option: Mechanical Fabrication and Production